Childhood Cultures in Transformation 30 Years of the UN Convention on the Rights of the Child in Action towards Sustainability - Eriksen Ødegaard, Elin; Spord Borgen, Jorunn (Brill, 2020)
This book investigates and uncover paradoxes and ambivalences that are actualised when seeking to make the right choices in the best interests of the child. The 1989 United Nations Convention on the Rights of the Child established a milestone for the 20th century. Many of these ideas still stand, but time calls for new reflections, empirical descriptions and knowledge as provided in this book. Special attention is directed to the conceptualisation of children and childhood cultures, the missing voices of infants and fragile children, as well as transformations during times of globalisation and change. All chapters contribute to understand and discuss aspects of societal demands and cultural conditions for modern-day children age 0-18, accompanied by pointers to their future. Readership: All engaged in children's rights, children's culture, generations, arts and public health education and those interested in understanding and change the paradoxes and complexity in children's lives.